2008
DOI: 10.1139/b08-072
|View full text |Cite
|
Sign up to set email alerts
|

Black-fruited hawthorns of western North America — one or more agamic complexes?This paper is one of a selection of papers published in the Special Issue on Systematics Research.This paper is dedicated to the memory of the University of Idaho botanist who got us thinking about the complexities of Northwest hawthorns: the late Steven J. Brunsfeld.

Abstract: Black-fruited hawthorns in North America comprise two taxonomic groups within the genus Crataegus , section Brevispinae and section Douglasianae. The first of these has recently been shown to be monospecific, consisting of the blueberry haw, Crataegus brachyacantha Sarg. & Engelm., of Louisiana and Texas. Crataegus section Douglasianae, however, comprises several taxa in a single clade that is not closely related to section Brevispinae, and that is now one of the best-studied groups of hawthorns at least i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Usually they show a basic structure similar to the classical scheme of Babcock & Stebbins (1938) based on the North American Crepis agamic complex: a few sexual progenitor species hybridized and formed a huge mass of allopolyploid, apomictic derivatives. Several authors have proposed to separate out the sexual progenitor species that are usually found at the diploid or low polyploid level (Grant, 1981;Dickinson & al., 2008;Hörandl & al., 2009;Burgess & al., 2015). These diploid taxa are usually self-sterile, outcrossing and their primary hybrids often exhibit a low female and male fertility.…”
Section: From Theory To Practice: Species Delimitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually they show a basic structure similar to the classical scheme of Babcock & Stebbins (1938) based on the North American Crepis agamic complex: a few sexual progenitor species hybridized and formed a huge mass of allopolyploid, apomictic derivatives. Several authors have proposed to separate out the sexual progenitor species that are usually found at the diploid or low polyploid level (Grant, 1981;Dickinson & al., 2008;Hörandl & al., 2009;Burgess & al., 2015). These diploid taxa are usually self-sterile, outcrossing and their primary hybrids often exhibit a low female and male fertility.…”
Section: From Theory To Practice: Species Delimitationmentioning
confidence: 99%
“…Recent RAD Seq studies on the complex, including more samples of R. ×hungaricus, rendered this species as highly polyphyletic (Karbstein & al., 2018). In the polyploids of Crataegus, phenetic clusters showed a great and often overlapping morphological variability (Dickinson & al., 2008). If such clusters were defined by morphology only, they may reflect an artificial assemblage of similar morphotypes of different evolutionary origins.…”
Section: From Theory To Practice: Species Delimitationmentioning
confidence: 99%
“…The Old World species are usually morphologically well-defined diploids, but common polyploidy and a high degree of hybridization blur clear species boundaries and the complex structure of populations still awaits elucidation. The situation with the New World species (especially the eastern North American species) is similar, but more complicated (Talent & Dickinson, 2005;Dickinson & al., 2008). Within the genus there are sexual self-incompatible diploids and facultatively asexual self-compatible taxa (mostly triploids and tetraploids) (Dickinson & al., 2008).…”
Section: Rosaceaementioning
confidence: 99%
“…The situation with the New World species (especially the eastern North American species) is similar, but more complicated (Talent & Dickinson, 2005;Dickinson & al., 2008). Within the genus there are sexual self-incompatible diploids and facultatively asexual self-compatible taxa (mostly triploids and tetraploids) (Dickinson & al., 2008). Apomixis within the genus is apospory with pseudogamous endosperm development (Campbell & al., 1991).…”
Section: Rosaceaementioning
confidence: 99%
See 1 more Smart Citation